2017
DOI: 10.1007/s10886-017-0844-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chemical Compositions of the Cuticle and Dufour’s Gland of Two Solitary Bee Species from Laboratory and Field Conditions

Abstract: Species-specific biochemistry, morphology, and function of the Dufour’s gland have been investigated for social bees and some non-social bee families. Most of the solitary bees previously examined are ground-nesting bees that use Dufour’s gland secretions to line brood chambers. This study examines the chemistry of the cuticle and Dufour’s gland of cavity-nesting Megachile rotundata and Osmia lignaria, which are species managed for crop pollination. Glandular and cuticular lipid compositions were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…The general pattern of CHC assorts well to the profile found in the North American blue orchard bee, O . lignaria [21,22] and comes up to the general pattern of Megachile rotundata [9,21,22]. Odd numbered alkanes and alkenes (C 23 , C 25 , C 27 ) dominated also the CHC profile of virgin Amegilla dawsonia , an anthophorinid ground-nesting, solitary bee [23].…”
Section: Discussionmentioning
confidence: 99%
“…The general pattern of CHC assorts well to the profile found in the North American blue orchard bee, O . lignaria [21,22] and comes up to the general pattern of Megachile rotundata [9,21,22]. Odd numbered alkanes and alkenes (C 23 , C 25 , C 27 ) dominated also the CHC profile of virgin Amegilla dawsonia , an anthophorinid ground-nesting, solitary bee [23].…”
Section: Discussionmentioning
confidence: 99%
“…Across a wide range of Hymenoptera the DG also contains hydrocarbons found on their cuticle. These include bumblebees (Oldham et al 1994 ), social Polistes (Dani et al 1996 ) and Ropalidia wasps (Mitra and Gadagkar 2014 ), as well as solitary wasps (Howard and Baker 2003 ) and solitary bees (Pitts-Singer et al 2017 ). Interestingly, in the stingless bee Melipona bicolor the DG has been lost in the workers (Abdalla et al 2004 ) but remains in the queen and contains hydrocarbons and esters, as found in many social Hymenoptera queens (Le Conte and Hefetz 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify volatiles, metabolomics techniques such as GC/MS can be used. However, within the plethora of substances that are produced during plant–animal interactions, it is still a challenge to pinpoint the compounds, or combinations thereof, which employ key ecological functions [ 118 , 122 , 126 , 127 ].…”
Section: Current Challengesmentioning
confidence: 99%